2021
DOI: 10.1021/acs.est.1c03292
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Toxicity Analyses from Different Endpoints: Are New Cyclic Disinfection Byproducts (DBPs) More Toxic than Common Aliphatic DBPs?

Abstract: In recent years, dozens of halogenated disinfection byproducts (DBPs) with cyclic structures were identified and detected in drinking water globally. Previous in vivo toxicity studies have shown that a few new cyclic DBPs possessed higher developmental toxicity and growth inhibition rate than common aliphatic DBPs; however, in vitro toxicity studies have proved that the latter exhibited higher cytotoxicity and genotoxicity than the former. Thus, to provide a more comprehensive toxicity comparison of DBPs from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…Briefly, two male and two female adult fish in each tank were separated the night before the collection of fertilized eggs. In a previous study of acute toxicity of aromatic DBPs on zebrafish embryos, the doses of DBPs ranged from 0.1 to 1000 μM . Exposure of zebrafish embryos to16 μM 2,6-DCBQ caused a high mortality rate (80%) .…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, two male and two female adult fish in each tank were separated the night before the collection of fertilized eggs. In a previous study of acute toxicity of aromatic DBPs on zebrafish embryos, the doses of DBPs ranged from 0.1 to 1000 μM . Exposure of zebrafish embryos to16 μM 2,6-DCBQ caused a high mortality rate (80%) .…”
Section: Methodsmentioning
confidence: 99%
“…70 Another study also demonstrated that the HepG2 cell cytotoxicity of DBPs was significantly correlated with both the CHO cell cytotoxicity and the T24 cell cytotoxicity, suggesting that the cytotoxicity results of HepG2 cells were reliable for the in vitro cytotoxicity evaluation of DBPs. 45 In our previous studies, HepG2 cells have been adopted for the cytotoxicity tests of iodinated DBPs, which was a well-established method for the cytotoxicity evaluation of DBPs. 42,46 Thus, we also adopted this method to clarify the comparative toxicity of the aliphatic and aromatic halogenated DBPs in swimming pool water and their incoming tap water in this study.…”
Section: Occurrence Of Aromatic Halogenated Dbps In Swimming Pool Wat...mentioning
confidence: 99%
“…It has been reported that the toxicity rank orders obtained from in vitro and in vivo bioassays had large discrepancies. 45 Thus, in future studies, in vivo toxicity assays may also be conducted to comprehensively clarify the risks posed by different categories of DBPs in swimming pool water. Furthermore, the concentration-cytotoxicity contributions were limited to the five categories of aliphatic halogenated DBPs and six categories of aromatic halogenated DBPs in this study, while other unknown categories of aliphatic and aromatic halogenated DBPs were not able to be included (especially for the large number of unknown aromatic halogenated DBPs).…”
Section: Concentration-cytotoxicity Contributions Of Different Dbp Ca...mentioning
confidence: 99%
“…23 An extensive new toxicology study of cyclic versus aliphatic DBPs by Wu et al demonstrates that aliphatic DBPs are much more cytotoxic, but cyclic DBPs have higher adverse developmental effects and acute toxicity in zebrafish embryos. 24 T h i s c o n t e n t i s Studies also show that >50% of total organic halogen (TOX) in chlorinated drinking water, >70% of TOX in chloraminated drinking water, and ∼40% of TOX in ozonated−chlorinated water are attributed to unknown DBPs, 25−29 and it was recently suggested that aromatic halo-DBPs might contribute ∼30% of the TOX in chlorinated drinking water. 23 To improve the safety of drinking water consumed daily by billions of people throughout the world, it is important to identify the structures of the unknown DBPs comprising a dominant portion of this water.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A recent paper by Diana et al suggests that non-nitrogenous DBPs, such as halocyclopentenoic acids, halofuranones, and haloquinones, may help to explain the risk of bladder cancer, and another study by Han et al suggests that aromatic halogenated DBPs might help to explain adverse developmental effects observed in epidemiologic studies . An extensive new toxicology study of cyclic versus aliphatic DBPs by Wu et al demonstrates that aliphatic DBPs are much more cytotoxic, but cyclic DBPs have higher adverse developmental effects and acute toxicity in zebrafish embryos …”
Section: Introductionmentioning
confidence: 99%